2001
DOI: 10.2116/analsci.17.957
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Tris(4-isopropyltropolonato)cobalt(III) on the Extraction of Lanthanoid(III) with 2-Thenoyltrifluoroacetone

Abstract: Synergistic enhancement of the extraction of lanthanoid(III) (Ln) with 2-thenoyltrifluoroacetone (Htta) in benzene has been found by the addition of tris(4-isopropyltropolonato)cobalt(III) (Co(ipt)3). The synergistic effect of Co(ipt)3 was ascribed to the formation of a 1:1 adduct of Ln(tta)3 with Co(ipt)3, i.e., a binuclear complex, in the organic phase. The adduct formation constant (beta s,1) determined by the extraction equilibrium analysis was reasonably consistent with that determined by spectrophotometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 20 publications
(33 reference statements)
1
34
0
1
Order By: Relevance
“…The adduct formation constants obtained were compared with those reported previously [2,3,5]. Table 1 lists the adduct formation constants (log  s,1 ) for the Ln(-diketone) 3 with the Co(III) chelate in benzene.…”
Section: Comparison Of the Adduct Formation Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adduct formation constants obtained were compared with those reported previously [2,3,5]. Table 1 lists the adduct formation constants (log  s,1 ) for the Ln(-diketone) 3 with the Co(III) chelate in benzene.…”
Section: Comparison Of the Adduct Formation Constantsmentioning
confidence: 99%
“…Tris(carbonato)cobalate(III) was prepared by the usual method [8]. Purification and identification of Co(ipt) 3 were performed in a same manner as reported previously [5]. The identification by the elemental analysis, 1 H-NMR (JEOL GSX-400), and HPLC (JASCO) showed that the Co(ipt) 3 obtained was a high purity and single geometric meridional isomer.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies of the synergistic extraction of Ln(III) have been comprehensively reported wherein Htta (2-thenoyltrifluoroacetone) was used as the -diketone together with Lewis bases with O-donor atoms such as tributyl phosphate and trioctylphosphine oxide [1][2][3]. The use of carboxylic acids [3][4][5], tris(-diketonato)metal(III) [6,7], linear polyethers [8,9], and crown ethers [10][11][12][13][14][15] as Lewis bases has also been reported. In general, the extractability of Ln(III) with the -diketone itself increases but the Solvent Extraction Research and Development, Japan, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent studies, it has been found that the extraction of lanthanoid ion (Ln 3+ ) with 2-thenoyltrifluoroacetone (Htta) is highly enhanced by the addition of tris(acetylacetonato)-metals(III) of chromium(III) 2 and cobalt(III), 3,4 tris(8-quinolinolato)cobalt(III) 5 or tris(4-isopropyltropolonato)cobalt(III) 6 in the organic phase. These remarkable phenomena were attributed to the adduct formation between Ln(tta)3 extracted and those inert chromium(III) or cobalt(III) chelates in the organic phase.…”
Section: Introductionmentioning
confidence: 99%